Off the charts: user engagement enhancers in election infographics. Issue 1 (2nd January 2022) - Amit-Danhi, Eedan R.; Shifman, Limor
ABSTRACT: In recent years, political discourse in digital spheres has seen a rise in the use of infographics. The paper addresses an unexplored question about this phenomenon: which characteristics are associated with higher levels of ostensive user engagement with political infographics in social media? We conceptualize ostensive user engagement as the outward-facing metrics afforded by a platform (e.g., like, share, and comment count) that serve both as means for self-presentation and shape the informational environment that others are exposed to. A corpus comprised of all infographics posted on Facebook by the four leading candidates in the 2016 US presidential campaign ( N = 252) was coded for cognitive, behavioral, and emotional characteristics. We found that two of the cognitively oriented dimensions enhanced engagement, while behavioral cues (calls to action) were, surprisingly, negatively linked. The inclusion of emotions did not show an overall association; however, a deeper look revealed a candidate-specific effect: anger was associated with greater engagement on Trump's infographics, and similarly, pleasure on Sanders'. In conclusion, we discuss the implications of our findings for understanding the informational environment shaped by engagement with infographics in light of the two seemingly opposing perceptions of internal and external authenticity.